Diffusion-weighted MRI in transient global amnesia and its diagnostic implications. (14th July 2020) - Szabo, Kristina; Hoyer, Carolin; Caplan, Louis R.; Grassl, Roland; Griebe, Martin; Ebert, Anne; Platten, Michael; Gass, Achim
Abstract : Objective: To analyze how the evidence of hippocampal diffusion-weighted imaging (DWI) lesions may support the clinical diagnosis of transient global amnesia (TGA). Methods: In this retrospective observational study, 390 consecutive patients with isolated TGA were analyzed, who were evaluated at our institution between July 1999 and August 2018. The size, location, and number of lesions and time-dependent lesion detectability were examined. The incidence of DWI lesions was reviewed with regard to different levels of clinical diagnostic certainty upon presentation to the emergency department. Results: Hippocampal DWI lesions were detected in 272 (70.6%) patients with TGA, with a mean of 1.05 ± 0.98 (range 0–6) and a mean lesion size of 4.01 ± 1.22 mm (range 1.7–8.6 mm). In the subgroups of lower diagnostic certainty (amnesia witnessed by layperson or self-reported amnestic gap), DWI was helpful in supporting the diagnosis of TGA in 76 (69.1%) patients. In 187 patients with information about the exact onset, DWI lesions were analyzed in relation to latency between onset and MRI. Lesions could be detected at all time points and up to 6 days after symptom onset in individual patients; the highest rate of DWI-positive MRI (93%) was in the 12–24 hours time window. Conclusion: MRI findings can support the diagnosis of TGA and may be particularly valuable in situations of low clinical certainty. DWI—ideally performed with a minimum delay of 20 hours after onset—should therefore be considered a useful adjunct to the diagnosis of TGA.